Adherence to physical exercise recommendations among type 2 diabetes patients during the COVID-19 pandemic. (2022) - Abate, Hailemichae Kindie; Ferede, Yohanes Mulu; Mekonnen, Chilot Kassa
Abstract: Background: In the era of the COVID-19 pandemic, nonadherence to the recommended physical exercise for diabetic patients is a difficult issue. Regular physical exercise is critical for reducing further complications of diabetes mellitus and the COVID-19 pandemic. The purpose of this study was to determine the predictors of type 2 adult diabetes patients' exercise recommendations during the COVID-19 pandemic. Methods: An institution-based cross-sectional study was conducted among 576 diabetes mellitus patients from August 1, 2020, to September 28, 2020. A systematic random sampling technique was used to select the study participants. An interviewer-administered questionnaire was used to collect the data. Frequency tables and percentages were used to explain the study variables. A binary logistic regression was used to investigate the relationship between the dependent and independent variables. Result: A total of 576 diabetes mellitus patients participated in the study, with a response rate of 99.3%. The overall prevalence of exercise adherence was 26.4%, whereas 73.6% were non-adherents to exercise recommendations. Rural residency (AOR = 1.95, 95% CI: 1.16–3.27) and COVID-19 related knowledge (AOR = 9.95, 95% CI: 41.14–5.24) were both strongly associated with exercise recommendations. Conclusion: In this study, only one-fourth of patients had exercised adherence during the era of the COVID-19 pandemic. Knowledge about COVID-19 was one of the factors that was strongly associated with adherence to exercise recommendations for diabetes patients. During the COVID-19 pandemic, encouraging home-based exercises can improve adherence to exercise recommendations.